2002
DOI: 10.1080/13678860210122643
|View full text |Cite
|
Sign up to set email alerts
|

In support of evidence-based management and research-informed HRD through HRD professional partnerships: an empirical and comparative study

Abstract: This article describes a programme of practice-grounded empirical management research set within an NHS Trust Hospital in the UK that was conducted as part of an HRD Professional Partnership of the kind advocated by Jacobs (1997). The research was concerned with identifying the criteria of managerial effectiveness at the middle and front-line levels of management using critical incident technique and factor analytic methods. The results are compared against those from an equivalent partnership research study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…In the NHS Trust study, sets of criteria were identified not only from the "top-down" perspective and "self" perspective, but also from the "bottom-up" perspective of subordinate managers and non-managers judging the effectiveness of their respective immediate superiors. Specific details of the findings from the three previous extant studies can be found in Hamlin (1988Hamlin ( , 1990Hamlin ( , 2002bHamlin ( , 2002c and Stewart (1998, 1999). The amount of qualitative and quantitative data obtained and analyzed in each study is shown in Table 1.…”
Section: Universalistic Models Of Managerial and Leadership Effectivementioning
confidence: 93%
See 1 more Smart Citation
“…In the NHS Trust study, sets of criteria were identified not only from the "top-down" perspective and "self" perspective, but also from the "bottom-up" perspective of subordinate managers and non-managers judging the effectiveness of their respective immediate superiors. Specific details of the findings from the three previous extant studies can be found in Hamlin (1988Hamlin ( , 1990Hamlin ( , 2002bHamlin ( , 2002c and Stewart (1998, 1999). The amount of qualitative and quantitative data obtained and analyzed in each study is shown in Table 1.…”
Section: Universalistic Models Of Managerial and Leadership Effectivementioning
confidence: 93%
“…However, there was an organizational imperative to identify the maximum number of factors for Anglia, and this led to the specific choice of alpha factor analysis rather than principal component analysis. It should be noted that both methods of analysis were used in the NHS Trust study and yielded near-identical factorial solutions (see Hamlin, 2002b).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 98%
“…Others have looked at publications as a means of closing the gap, including the ASTD "What Works" series of short volumes describing research-based solutions on topics of most relevance to practitioners (Dilworth & Redding, 1999) and the AHRD stable of journals that provide HRD scholars outlets for their best work: outlets that can reach many stakeholders of HRD and influence practice (Roth, 2003). On the production and use of research, several examples of research projects directly relate to research and practice (Dilworth & McClernon, 2000), including published examples of practitioner-academic research partnerships (Hamlin, 2002), and awards have been created to recognize those who excel in linking research and practice .…”
Section: What Has Been Tried Already To Close the Gap?mentioning
confidence: 98%
“…Hamlin (2002) and Holton (2004) have argued the need for a shift to evidence-based practices, which have some reasonable level of scientific support-a standard more possible to achieve than the lofty but impractical standard of scientific proof (Holton).…”
Section: Practice and Practitionersmentioning
confidence: 98%
See 1 more Smart Citation